Entrepreneurship and effective small business management - Scarborough, Norman M. (Pearson, 2015)
For undergraduate and graduate courses in entrepreneurship and/or small business management. Discover how to successfully launch and manage a small business. Open your students' minds to the possibilities, challenges, and rewards of becoming a small business owner with Entrepreneurship and Effective Small Business Management. This text provides students with the tools they need in order to launch and manage a small business. This Eleventh Edition continues to provide students with a practical, hands-on approach to launch a business that has the greatest chance for success. This edition features ten new cases and the most recent statistics, studies, surveys, and research about entrepreneurship and small business management.